Peranan Pemerintah Desa dalam Meningkatkan Kualitas Pelayanan Administrasi kepada Masyarakat - Erdipa Panjaitan; Rosmala Dewi; Nina Angelia (PERSPEKTIF, 2019)
Role is a set of expectations imposed on an individual who occupies a certain social position. This  study  aims  to  determine  the  role  of  village  government  in  improving  the  quality  of administrative services to the community in the Office of Village Head Aek Korsik. The method of research  used  is  a  descriptive qualitative  method approach  that  focuses  on  the  role  of  village  government in improving the quality of administrative services to the community at the Head Office of Aek Korsik Village Aek Kuo Sub-district, North Labuhanbatu Regency. The results  showed  that  the quality of administrative services in the Head Office of Aek Korsik Village Aek Kuo Sub-district, North Labuhanbatu  Regency  has  applied  Tangible,  Reliability,  Responsiveness,  Assurance,  and Emphaty dimensions and their indicators. However, there are still some indicators that have not run in accordance with the expectations of the community, including the inconvenience of service places including facilities and infrastructure that have not been complete, the employee has not effectively used SOP (Standard Operating Procedure) in the service process, and there are still employees who are not friendly in the service process.